The effect of the difference in the temperature of the environment in the aerobic capacity of the students of the Faculty of Physical Education Index - Hussein, Eman; Loay, Gaith (Journal of Physical Education, 2015)
The study aimed to: Identify the impact of the difference in the temperature of the environment in an aerobic capacity for students of the physical education college. The researcher used the descriptive survey manner for the purpose of achieving the goal of the study, the research sample was selected research community deliberate They are students of the college of Physical Education - University of Baghdad, as the number of members of the research sample (60) students from the three stages (first - second - third), were tested at a temperature (16-20) and then re-test their degree (36-40) as well as the experience of the exploratory. The researcher used the bag statistical system (SPSS) The researcher concluded the following: 1. For students of Physical Education physical performance at low temperatures is more efficient than high temperatures. 2. increase in the rate of aerobic capacity during low temperatures than in high temperature Key words: temperature, aerobic capacity, performance physical, Environment